HUBUNGAN MUTASI PADA GEN LEPTIN EXON 2 DENGAN BOBOT LAHIR, PERTAMBAHAN BOBOT BADAN DAN BOBOT SAPIH SAPI BALI - Nena Hilmia; Dedi Rahmat; Dudi Dudi (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2019)
The one of genes that play an important role in the body metabolism that is closely related to productivity is the Leptin gene. This study aims to determine the assosiation polymorphism of exon 2 Leptin gene based on Single Nucleotide Polymorphism (SNP) with birth weight of Balinese cattle. This study used 47 DNA of Balinese cattle, their birth weight (BW), average daily gain (ADG) and yearling weight (YW) data, that were obtained from BPTU HPT Pulukan Bali. The isolation of DNA using a high salt concentrated method and DNA target was duplicated by PCR machine. Analysis genetic mutation of Leptin genes was performed by evaluating SNP in Exon 2 at R25C and R25H, from direct sequencing results, using Bioedit and MEGA 5.2 program. The association of Leptin gene polymorphism with BW, ADG and YW were analyzed using variance analysis. The result showed that there were For genotypes based on SNP R25C and R25H, ie CC, CT, CA, and AA. There were no assosiation between Leptin gene polymorphism with birth weight (BW), average daily gain (ADG) and yearling weight (YW) on Balinese cattle.